Aneurysmal bone cyst of proximal fibula treated with en-bloc excision: a rare case report - Wadhawan, Piyush; Agrawal, Atul; Khera, Ruchit (International Journal of Research in Orthopaedics, 2019)
Aneurysmal bone cysts (ABCs) are benign but locally destructive, blood filled reactive lesions of the bone. Although a wider age group may be affected, most commonly they are seen in patients younger than 20 years of age, with a slight female preponderance. Most common sites include metaphysis of femur followed by tibia and then humerus. Vertebral lesions involving the posterior elements are common.Aneurysmal bone cyst of proximal fibula is a rare and uncommon. Here, we report a case of 13 year old female with classic histologic, clinical, and radiographic findings that was treated by en bloc resection.